Ethnobotany of Traditional Medicinal Plants in the Lumban Sipahutar Community, North Sumatra, Indonesia - Lastiur Sipahutar; Dian Pardede; Grace Siahaan; Wikky Pramudya; Rahel Rajagukguk; Feby Situmorang; Intan Siburian; Ochatun Sakdiyah; Masni Veronika Situmorang (Young Journal of Social Sciences and Humanities, 2026)
Community knowledge regarding the use of traditional medicinal plants represents an important component of local wisdom that should be documented to support the conservation of biodiversity and the preservation of traditional healthcare systems. This study aims to inventory the medicinal plant species utilized by the people of Lumban Sipahutar, North Sumatra, Indonesia, and to document their botanical classification, plant parts used, preparation methods, and traditional medicinal applications. The research employed an ethnobotanical approach using a qualitative descriptive method. Data was collected through field observations, in-depth interviews, documentation, and morphological identification of plant specimens, which were subsequently classified taxonomically to the species level. The findings identified 16 medicinal plant species traditionally used by the local community for healthcare purposes. These species belong to various botanical families, with leaves being the most frequently utilized plant part, followed by rhizomes, stems, roots, fruits, and flowers. The plants are commonly prepared by boiling, pounding, infusion, or direct application. Most species are traditionally used to treat digestive disorders, respiratory ailments, fever, and wound-related conditions. The findings demonstrate that the people of Lumban Sipahutar continue to preserve a traditional healthcare system based on local biological resources, highlighting its potential contribution to biodiversity conservation and the development of phytopharmaceutical research in Indonesia.